Evolution of coronary artery calcium and absolute myocardial perfusion after percutaneous revascularization: a 3-year serial hybrid [15O]H2O PET/CT imaging study. (8th February 2021) - De Winter, RW; Schumacher, SP; Stuijfzand, WJ; Van Diemen, PA; Everaars, H; Bom, MJ; Van Rossum, AC; Van De Ven, PM; Appelman, Y; Lemkes, JS; Verouden, NJ; Nap, A; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background. The value of serial coronary artery calcium (CAC) scores to predict changes in absolute myocardial perfusion and epicardial vasomotor function is poorly documented. Purpose.  This study explored the association between progression of CAC score and changes in absolute myocardial perfusion. Methods. Fifty-three patients with single-vessel coronary artery disease (CAD) underwent [15O]H2O Positron Emission Tomography/Computed Tomography at 1 month (baseline), 1 year, and 3 years after percutaneous coronary intervention (PCI) to assess CAC scores, hyperemic myocardial blood flow (hMBF), coronary flow reserve (CFR) and cold pressor test MBF (CPT-MBF), within the context of the VANISH (Impact of Vascular Reparative Therapy on Vasomotor Function and Myocardial Perfusion) trial. Relationships between baseline CAC score and evolution of perfusion indices were explored with a mixed model-analysis. Results. Baseline CAC score was 0 in 9%, 0.1-99.9 in 40%, 100-399.9 in 36% and ≥400 in 15% of patients, respectively. In higher baseline CAC groups, scores increased more over time (overall p < 0.01). Mixed model-analysis allowed for averaging perfusion indices over all time points: hMBF (3.74 ± 0.83; 3.33 ± 0.79; 3.08 ± 0.78 and 2.44 ± 0.74 mL·min-1·g-1) and CFR (3.82 ± 1.12; 3.17 ± 0.80; 3.19 ± 0.81; 2.63 ± 0.92) were lower among higher baseline CAC  groups (p < 0.01; p = 0.03). However, no significant interaction was found between baseline CAC groups and time after PCI for all perfusion indices, denoting that evolution of perfusion indices over time were not significantly different between CAC groups. Furthermore, CAC progression was not correlated with evolution of hMBF (r = 0.08, p = 0.57), CFR (r = 0.09, p = 0.53) or CPT-MBF (r = 0.03, p = 0.82) during 3 years follow-up. Conclusions. Higher baseline CAC was associated with lower hMBF and CFR. However, both baseline CAC and its progression were not associated with evolution of absolute hMBF, CFR and CPT-MBF over time, suggesting that CAC score and progression of CAC are poor indicators of change in absolute myocardial perfusion.